2012
DOI: 10.1073/pnas.1212207110
|View full text |Cite
|
Sign up to set email alerts
|

Morphing between expressions dissociates continuous from categorical representations of facial expression in the human brain

Abstract: Whether the brain represents facial expressions as perceptual continua or as emotion categories remains controversial. Here, we measured the neural response to morphed images to directly address how facial expressions of emotion are represented in the brain. We found that face-selective regions in the posterior superior temporal sulcus and the amygdala responded selectively to changes in facial expression, independent of changes in identity. We then asked whether the responses in these regions reflected catego… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

14
89
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(103 citation statements)
references
References 48 publications
(74 reference statements)
14
89
0
Order By: Relevance
“…In line with the classic account proposed by Haxby et al (2000), the FFA has been shown to be sensitive to repetitions of face identity (Rotshtein, Henson, Treves, Driver, & Dolan, 2005;Winston, Henson, Fine-Goulden, & Dolan, 2004;Yovel & Kanwisher, 2005), while the STS was found to be sensitive to dynamic aspects of face perception such as repetitions of expression (Andrews & Ewbank, 2004;Ganel, Valyear, Goshen-Gottstein, & Goodale, 2005;Harris, Young, & Andrews, 2012;Winston, Henson, Fine-Goulden, & Dolan, 2004). A recent fMRI adaptation study by Harris, Young, and Andrews (2014) has suggested that brain regions involved in the recognition of facial identity or expression are differentially sensitive to surface-based versus edge-based visual signals.…”
Section: Introductionmentioning
confidence: 50%
See 1 more Smart Citation
“…In line with the classic account proposed by Haxby et al (2000), the FFA has been shown to be sensitive to repetitions of face identity (Rotshtein, Henson, Treves, Driver, & Dolan, 2005;Winston, Henson, Fine-Goulden, & Dolan, 2004;Yovel & Kanwisher, 2005), while the STS was found to be sensitive to dynamic aspects of face perception such as repetitions of expression (Andrews & Ewbank, 2004;Ganel, Valyear, Goshen-Gottstein, & Goodale, 2005;Harris, Young, & Andrews, 2012;Winston, Henson, Fine-Goulden, & Dolan, 2004). A recent fMRI adaptation study by Harris, Young, and Andrews (2014) has suggested that brain regions involved in the recognition of facial identity or expression are differentially sensitive to surface-based versus edge-based visual signals.…”
Section: Introductionmentioning
confidence: 50%
“…Activity in the FFA has been shown to be larger in response to expressive versus neutral faces (Furl, Henson, Friston, & Calder, 2013;Vuilleumier, Armony, Driver, & Dolan, 2001), and adaptation effects by repetitions of facial expressions have been found in the FFA (Ganel et al, 2005;Harris et al, 2012;Fox, Moon, Iaria, & Barton, 2009). Furthermore, there is also fMRI evidence that the STS is sensitive to repetitions of face identity (Fox et al, 2009).…”
Section: Introductionmentioning
confidence: 91%
“…These structures form the core components of an influential neurocognitive model of the human face-processing system (Haxby et al, 2000) that has received broad support in terms of its general claims (GrillSpector et al, 2004;Winston et al, 2004;Fox et al, 2009), although more recent work continues to fine-tune our understanding of the component nodes of this network and their functional sensitivities (Said et al, 2010;van den Hurk et al, 2011;Harris et al, 2012;Mende-Siedlecki et al, 2013;Baseler et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Answering this question is complicated by the fact that many parts of the brain are involved (Adolphs 2002;Vuilleumier & Pourtois 2007). ere is evidence that both the amygdala (Harris et al 2012(Harris et al , 2014 and also some cortical structures (Bay & Taylor 2003) respond categorically to expressions of emotion; and that intervening in the operations of the somatosensory cortex can impair categorisation (Pitcher et al 2008; see also Banissy et al 2011). To my knowledge, so far it is only for happy and fearful stimuli that we have direct evidence from both neurophysiological (Campanella et al 2002) and behavioural measures (Williams et al 2005) of categorisation occurring in perceptual processing.…”
mentioning
confidence: 99%